Multistatic image entropy based autofocus - Brisken, Stefan; Martorella, Marco; Worms, Josef G. (2013 14th International Radar Symposium (IRS), 2013)
We introduce a multistatic extension of the popular image entropy based ISAR autofocus algorithm. Instead of only estimating the target's range history, the new method is capable to estimate the full trajectory. It is not subject to geometrical limitations nor is coherency in the signal return between different sensors required. The efficiency of the new method is proved with experimental data.